Plumbing - Babbitt, Harold E. (New York : McGraw-Hill, 1960)
This is textbook on plumbing which covers topics like: elements of plumbing; hydraulics and pneumatics; water supplies; storage tanks; hot water supplies; interior fire protection; installation of drainage; bathing; kitchen, washing and other fixtures; maintenance and repairs and others.
Includes bibliographical references and index.
lje 22/01/2019
Loans
Keywords: Plumbing